The Role of Infrastructure in the Province's Gross Regional Domestic Product on the Island of Sumatra - Agil Saputri; Romi Gunawan (Indonesian Journal of Banking and Financial Technology, 2025)
Indonesia's infrastructure, especially in Sumatra, is considered inadequate to support the strength of the Indonesian economy in facing free market competition in the global era, lack of accessibility to reach remote areas so that the Gross Regional Domestic Product (GRDP) value in the region has a fairly small value. The study aims to determine the effect of road infrastructure, health facilities, educational facilities, water infrastructure, and electricity infrastructure on the level of gross regional domestic product (GRDP) in Sumatra, for the purpose of this study is to determine the effect of road length infrastructure, health facilities, educational facilities, clean water distribution and electricity partially on gross regional domestic product. This study uses a panel data model with the selected model, namely the Random Effect Model (REM). This study focuses on all provinces in Sumatra, namely 10 provinces in 2019-2023. The results of this study have a simultaneous effect where the relationship with the independent variables is Road Length Infrastructure (X1), Health Facilities (X2), Educational Facilities (X3), Clean Water Distribution (X4) and Electricity (X5) against the dependent variable, namely Gross Regional Domestic Product (Y). Then, the test results for each dependent variable on the variables of Road Length (X1), Health Facilities (X2), Education Facilities (X3), and Electricity (X5) significantly influenced Gross Regional Domestic Product (Y), while the test of Clean Water Distribution (X4) on Gross Regional Domestic Product (Y) did not have a significant effect. This is thought to be due to the uneven distribution of Clean Water Distribution facilities or infrastructure in Sumatra.